Leveraging Upscale Homestays for Sustainable Tourism and Local Community Livings in Sikkim - India - Dam, Supriya (Language Assistance, 2025)
The study examines the homestay landscape in the Indian Himalayan Region (IHR), with a particular focus on Sikkim, India. Homestays offer alternative accommodations for visitors in natural settings, providing a peaceful retreat away from the hustle and bustle of towns. They also play a crucial role in spreading tourism from crowded areas to less-frequented destinations and serve as a direct source of income for local communities. Recent data reveals that homestays account for 51.36 percent of total accommodations, indicating a shift towards homestays as part of a sustainable tourism strategy. However, findings show that homestay owners face economic challenges in maintaining their businesses. For instance, in Gangtok, the hotel border capacity density (BCD) reaches 18.9 per square kilometer, raising concerns about the area's environmental fragility. The recent inclusion of the Pakyong and Soreng districts in the eastern and western zones, which have sizeable number of homestays, is viewed as a positive step towards spreading tourism activity. However, the results indicate that the strategy of directing tourists to homestays from overcrowded urban areas has not met its objectives. The study suggests attracting high-end tourists to homestays by offering modern amenities and a welcoming, homelike atmosphere, which may lead to the emergence of special interest homestays.